2012
DOI: 10.1152/ajpheart.01120.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking macrophage 12/15-lipoxygenase are resistant to experimental hypertension

Abstract: In mouse arteries, Alox15 [leukocyte-type 12/15-lipoxygenase (LO)] is assumed to regulate vascular function by metabolizing arachidonic acid (AA) to dilator eicosanoids that mediate the endothelium-dependent relaxations to AA and acetylcholine (ACh). We used Alox15(-/-) mice, made by targeted disruption of the Alox15 gene, to characterize its role in the regulation of blood pressure and vascular tone. Systolic blood pressures did not differ between wild-type (WT) and Alox15(-/-) mice between 8-12 wk of age, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 57 publications
3
41
0
Order By: Relevance
“…Initially, EETs, H 2 O 2 and C-type natriuretic peptide were described to function as EDHFs 2426 in mice. As we recently demonstrated, LO metabolites of AA also mediate EDHF activity in murine resistance arteries 13, 22 . The EDHF activity in these arteries is inhibited by LO and hydroperoxide isomerase inhibitors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Initially, EETs, H 2 O 2 and C-type natriuretic peptide were described to function as EDHFs 2426 in mice. As we recently demonstrated, LO metabolites of AA also mediate EDHF activity in murine resistance arteries 13, 22 . The EDHF activity in these arteries is inhibited by LO and hydroperoxide isomerase inhibitors.…”
Section: Discussionmentioning
confidence: 54%
“…While 15-LO-1 plays an important role in endothelium-dependent relaxation in rabbit arteries 2 , the LO that contributes to vascular relaxations in the mouse has not been identified. In a recent study 13 we found no aortic expression of Alox15, the mouse homologue of rabbit and human 15-LO-1 11, 14, 15 . As a consequence, there was no difference between vascular relaxations to ACh in aortas from wild type (WT) and Alox15 knockout mice.…”
Section: Introductionmentioning
confidence: 70%
“…53 Also mice lacking macrophage 12/15 LO have been shown to be resistant to L-NAME or deoxycorticosterone-salt induced hypertension. 54 Ang II is known to cause hypertension by increasing oxidative stress in subfornical organ (SFO) of circumventricular organs and via its projections to paraventricular nucleus and from there to the brain stem, finally resulting in increased sympathetic activity. 55 cPLA 2 α is also present in the brain 13,16 and intracerebroventricular administration of PGE2 increases sympathetic nervous activity, vasopressin release and BP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chronic hypoxia and hypercholesterolemia enhanced ALOX15 mediated vasorelaxation in rabbit arteries [223, 224]. More direct evidence for the in vivo relevance of ALOX15 in blood pressure regulation was recently provided by experiments with ALOX15-deficient mice [225]. Although systolic blood pressures did not differ between these mice and wild-type controls Alox15 −/− -mice exhibited higher resistance towards L-NAME- and high-salt-induced hypertension than corresponding controls.…”
Section: Biological Function Of Mammalian Lox Isoformsmentioning
confidence: 99%
“…Interestingly, injection of wild-type peritoneal macrophages, which are a major source of ALOX15 in mice, into ALOX15-deficient animals abolished their resistance toward L-NAME-induced hypertension. Inversely, wildtype mice acquired resistance to L-NAME-induced hypertension after depletion of macrophages by clodronate injection [225]. …”
Section: Biological Function Of Mammalian Lox Isoformsmentioning
confidence: 99%